The Nusantara Interpretation By Bugis Scholars: Social And Local Dimensions Of Al-Munir Tafsir By Agh. Daud Ismail - Haris, Abd. Haris; Nurfaika, Nurfaika (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Sekolah Tinggi Ilmu Al-Qur'an Al Multazam Kuningan, 2025)
This essay explains the Nusantara interpretation, specifically the Al-Munir Tafsir authored by AGH Daud Ismail, a prominent Bugis scholar from South Sulawesi. The interpretation plays a significant role in conveying Quranic messages in alignment with the social conditions surrounding the exegete. This study aims to investigate and analyze selected Quranic verses, subsequently examining their significance within the local societal context. The research employs a qualitative methodology utilizing literary review techniques, with a focused analysis of the Bugis Al-Munir Tafsir. Moreover, a phenomenological approach is utilized to establish connections between textual interpretation and social contexts. The article’s findings reveal that AGH. Daud Ismail developed a contextual interpretation model that demonstrates profound sensitivity to the social dynamics of Bugis society. This is evident in the strategic selection of Lontarak linguistic expressions readily comprehensible to the Bugis community. This research discovered that the Al-Munir Tafsir transcends mere translation and interpretation of the Quran based on the exegete's immediate requirements; instead, its interpretative approach facilitates the community's understanding of the Quranic text. Specifically, this research highlights the author's utilization of local language and linguistic expressions as a methodological strategy to transform Quranic messages into the cultural reality of Bugis society. This study is anticipated to contribute to enriching the scholarly landscape of Nusantara tafsir studies by presenting an interpretation model that is responsively attuned to the social contexts of the Bugis community in South Sulawesi, with broader implications for advancing more contextual and inclusive interpretation methodologies.